Chemical and microbial quality evaluation of fresh tomato and its processed products using FTIR, SEM and GC-MS - Ochida , Comfort Onyeche; Itodo , Adams Udoji; Anhwange , Benjamin Asen; Nwanganga, Promise Adaku; Abah, Christopher Nyerere (Journal of Postharvest Technology, 2019)
In this study, fresh tomatoes (Lycopersicon esculentum Mill) and the different forms of preserved tomatoes (sun dried, paste and oven dried) were investigated for the effects of preservation on their distinctive quality. Some quality parameters such as microbial load and volatile compounds analysis were carried out. Scanning electron microscope (SEM) and Fourier transform infrared (FTIR) were employed to observe possible variation in the microstructures and spectral characteristics respectively. The fresh tomato had the highest microbial load followed by the sundried with reasons attributed to poor handling, unhygienic environment and generally unwholesome processing conditions. The FTIR spectral of control and processed samples showed slight variations in peak positions. SEM images of the fresh and preserved tomatoes showed some level of micro-structural dissimilarities. A total of 63 major volatile compounds were identified in the various samples and grouped in relation to the chemical class they belong. General highlights from this research showed that the exposure of tomatoes to various preservation techniques results to the loss of some nutrients compared to the fresh food item.